Damage limitation - A new spillway aerator - Ozturk, Mualla; Aydin, Mehmet Cihan; Aydin, Seckin (My University, 2008)
A new approach has been developed for aerators designed to prevent cavitation on dam spillways. The approach has been developed to overcome the typical problem with conventional spillway aerators that has the potential to be submerged because of low Froude numbers and not enough air entrainments. The approach comes in the form of a new aerator type, which is the bottom-inlet aerator. Greater performance and better air mixture in a wide chute is provided by the new aerator type.
Keywords: Salinity measurement; Spillways; aeration; cavitation; dam; spillway; Air mixtures; Damage limitation; New approaches; Air entrainment